2015
DOI: 10.11646/phytotaxa.236.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Cyathus lignilantanae sp. nov., a new species of bird’s nest fungi (Basidiomycota) from Cape Verde Archipelago

Abstract: Cyathus lignilantanae sp. nov. is described and illustrated on the basis of morphological and molecular data. Specimens were collected on Santiago Island (Cape Verde), growing on woody debris of Lantana camara. Affinities with other species of the genus are discussed. ResumenSobre la base de datos morfológicos y moleculares se describe e ilustra Cyathus lignilantanae sp. nov. Los especímenes se recolectaron en la isla de Santiago (Cabo Verde), creciendo sobre restos leñosos de Lantana camara. Se discuten las a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…gasteroid and corticioid) and to describe new species (e.g. [ 36 38 ]). Unfortunately, however, even if molecular analysis detects a new species, some authors do not follow through by describing and naming it.…”
Section: Discussionmentioning
confidence: 99%
“…gasteroid and corticioid) and to describe new species (e.g. [ 36 38 ]). Unfortunately, however, even if molecular analysis detects a new species, some authors do not follow through by describing and naming it.…”
Section: Discussionmentioning
confidence: 99%
“…However, C. stercoreus is distinguished by the absence of striae in the peridium, inconspicuous emplacement, woolly tomentum, endoperidium with platinum bright colour, spores not exceeding 31 μm in length, and spore walls less than 2.5 μm in thickness. Cyathus lignilantanae has basidiomata above 7 mm in height, internal wall with platinum bright colour, peridioles with 2–2.5 × 1.5–2 mm, spores smaller than 25.5 μm in length and 17 μm in width, and with thin walls not reaching 2 μm ( Martín et al 2015 ).…”
mentioning
confidence: 99%
“…Barcoding sequences also help in identification of the species Tulostoma brumale in some collections, when a brown ring zone around the mouth is absent or not clearly defined, or T. simulans, which also is described as having a brown mouth zone (Jeppson et al, 2017). However, as indicated by many authors (Schoch et al, 2012;Jeppson et al, 2013;Martín et al, 2015;Sousa et al, 2017), the ITS marker alone is not enough to infer the phylogenetic relationship among species, and it is necessary to study at least two or three markers to clearly delimitate the taxa (such as Tef 1a used in the analyses by Jeppson et al (2017), RPB2, or translation elongation factor 1-alpha). Moreover, in our study more collections should be found and studied to define Tulostoma sp.…”
Section: Discussionmentioning
confidence: 99%